Implementation of E-Sakip Towards Improving the Quality of Performance Accountability Evaluation Reports in the Ministry of Defense Through the ESR Application - Mulya Naya; Iwan Kurniawan Subagja; Azis Hakim (Dinasti International Journal of Digital Business Management, 2026)
E-Sakip is an electronic Government Agency Performance Accountability System (E-SAKIP) application that aims to facilitate the process of monitoring and controlling the performance of Work Units within Government Agencies in order to improve the accountability and performance of work units in particular and the performance of Agencies in general. This application is used by government agencies (central and regional) to plan, monitor, and report performance digitally. This study was conducted with the aim of determining the effect of the e-SAKIP application on the performance of Work Units within the Ministry of Defense. This study uses a quantitative method, namely research by obtaining data in the form of numbers or quantitative data that is quantified, through a data collection process using a questionnaire or a list of questions given to all selected respondents. The implementation of the E-SAKIP application is expected to be able to increase transparency, effectiveness of performance management, and support the creation of good governance. With this system, government agencies can make more appropriate decisions based on accurate and integrated performance data